Quality Service Strategy in Improving Performance of Puskesmas Service Area of Mranggen District - Nanang Wahyudin (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
This study aims to analyze the quality of services available at the health center of Mranggen in order to formulate a strategy to improve the quality of health services of Puskesmas by analyzing the importance and level of performance in six dimensions of service quality (Tangibles, Reliability, Responsiveness, Assurance, Empathy and Accessibility) to produce performance (performance) that can satisfy customers. The data analysis of this research was conducted by qualitative descriptive method, to answer the problem formulation about how to improve the quality of health service of Mranggen in accordance with the quality standard set by the Government, then used